Burden of pneumocystis pneumonia in HIV-infected adults in sub-Saharan Africa: a systematic review and meta-analysis. Issue 1 (December 2016) - Wasserman, Sean; Engel, Mark; Griesel, Rulan; Mendelson, Marc
Abstract Background Seroprevalence data and clinical studies in children suggest that the burden of pneumocystis pneumonia (PCP) in Africa may be underestimated. We performed a systematic review to determine the prevalence and attributable mortality of PCP amongst HIV-infected adults in sub-Saharan Africa. Methods We searched Pubmed, Web of Science, Africa-Wide: NiPAD and CINAHL, from Jan 1 1995 to June 1 2015, for studies that reported the prevalence, mortality or case fatality of PCP in HIV-infected adults living in sub-Saharan African countries. Prevalence data from individual studies were combined by random-effects meta-analysis according to the Mantel-Haenszel method. Data were stratified by clinical setting, diagnostic method, and study year. Results We included 48 unique study populations comprising 6884 individuals from 18 countries in sub-Saharan Africa. The pooled prevalence of PCP among 6018 patients from all clinical settings was 15 · 4 % (95 % CI 12 · 9–18 · 0), and was highest amongst inpatients, 22 · 4 % (95 % CI 17 · 2–27 · 7). More cases were identified by bronchoalveolar lavage, 21 · 0 % (15 · 0–27 · 0), compared with expectorated, 7 · 7 % (4 · 4–11 · 1), or induced sputum, 11 · 7 % (4 · 9–18 · 4). Polymerase chain reaction (PCR) was used in 14 studies (n  = 1686). There was a trend of decreasing PCP prevalence amongst inpatients over time, from 28 % (21–34) in the 1990s to 9 % (8–10) after 2005. The case fatality rate was 18 · 8 % (11 · 0–26 · 5), and PCP accounted for 6 · 5 % (3 · 7–9 · 3) of study deaths. Conclusions PCP is an important opportunistic infection amongst HIV-infected adults in sub-Saharan Africa, particularly amongst patients admitted to hospital. Although prevalence appears to be decreasing, improved access to antiretroviral therapy and non-invasive diagnostics, such as PCR, are needed.